Two-dimensional metallic tantalum disulfide as a hydrogen evolution catalyst. Issue 1 (December 2017) - Shi, Jianping; Wang, Xina; Zhang, Shuai; Xiao, Lingfeng; Huan, Yahuan; Gong, Yue; Zhang, Zhepeng; Li, Yuanchang; Zhou, Xiebo; Hong, Min; Fang, Qiyi; Zhang, Qing; et al.
Abstract Two-dimensional metallic transition metal dichalcogenides are emerging as prototypes for uncovering fundamental physical phenomena, such as superconductivity and charge-density waves, as well as for engineering-related applications. However, the batch production of such envisioned transition metal dichalcogenides remains challenging, which has hindered the aforementioned explorations. Herein, we fabricate thickness-tunable tantalum disulfide flakes and centimetre-sized ultrathin films on an electrode material of gold foil via a facile chemical vapour deposition route. Through temperature-dependent Raman characterization, we observe the transition from nearly commensurate to commensurate charge-density wave phases with our ultrathin tantalum disulfide flakes. We have obtained high hydrogen evolution reaction efficiency with the as-grown tantalum disulfide flakes directly synthesized on gold foils comparable to traditional platinum catalysts. This work could promote further efforts for exploring new efficient catalysts in the large materials family of metallic transition metal dichalcogenides, as well as exploiting their applications towards more versatile applications. Metallic transition metal dichalcogenides are important materials for catalysis, but scalable and controllable preparation methods are scarce. Here, the authors synthesize 2H-TaS2 as centimetre-scale films of tunable thickness and show they are an efficient catalyst for hydrogen evolution.